(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2025)
This study analyzed the proximate composition of Sacha inchi oil press-cake (SIOPC) and its effects on the physicochemical and sensory properties of chicken patties. Five formulations were prepared: a control (F0) with 0% SIOPC and 10% fat, and four variations—F1 (2.5% SIOPC + 7.5% fat), F2 (5% SIOPC + 5% fat), F3 (7.5% SIOPC + 2.5% fat), and F4 (10% SIOPC + 0% fat). Proximate analysis of SIOPC revealed a remarkable protein (54.20%) and fat (22.87%) contents. Moreover, the addition of SIOPC in chicken patties significantly increased the ash content, while reducing the fat level (p<0.05). Fat replacement with SIOPC reduced pH and cooking loss (p<0.05) while improving water holding capacity and cooking yield. Color analysis showed no effect on lightness (L*) but decreased redness (a*) and yellowness (b*) (p<0.05). Texture profile analysis indicated significant differences (p<0.05) in hardness, chewiness, and resilience, but not in cohesiveness and springiness (p>0.05). Sensory evaluation found no significant differences (p>0.05) in color, aroma, taste, or overall acceptance, though F2 received the highest score among SIOPC-enriched formulations. Overall, SIOPC shows promise as a fat replacer in reduced-fat chicken patties.